The Secret History of the American Empire : the truth about economic hit men, jackals, and how to change the world - Perkins, John (New York : Plume Book, 2008)
From the author of the "New York Times" bestseller "Confessions of an Economic Hit Man" comes an expos of international corruption. Perkins suggests how Americans can work to create a more peaceful and stable world for future generations.
Includes Bibliographical References and Index.
Keywords: BUSINESS & ECONOMICS International; businesses (business enterprises)